Examining real-time physical activity in adolescents using the Multi-Process Action Control Model: An ecological momentary assessment study - Sheereen Harris; Denver Brown; Sara King-Dowling; John Cairney; Matthew Kwan (Bern Open Publishing, 2024)
The purpose of this study was to examine real-time associations between reflective (i.e., state motivation), regulatory (i.e., self-control), and reflexive (i.e., habit) constructs from the Multi-Process Action Control (M-PAC) model and real-time moderate-to-vigorous physical activity (MVPA) behaviour among adolescents using ecological momentary assessments. One hundred and ninety adolescents (Mage = 15.76 ± .47 years; n = 101 males) wore an accelerometer for seven consecutive days and responded to digital survey prompts up to four times daily during the after-school periods. MVPA in the 60-minute time window following each survey prompt was recorded. Multilevel mixed-effects linear and logistic models were computed with disaggregated between- and within-person effects to analyze the data. Results from both linear and logistic multilevel models revealed adolescents with higher state motivation in general and experiencing higher state motivation than one's typical levels were associated with engaging in more MVPA and higher likelihood of engaging in ≥10 minutes of MVPA. Engaging in activities less consistent with habitual behaviours were associated with more MVPA and higher likelihood of engaging in ≥10 minutes of MVPA. By contrast, self-control was not associated with MVPA. Results from this study extend previous work demonstrating the importance of conscious and non-conscious processes on MVPA behaviour by examining associations in real-time using intensive longitudinal methods. Collectively, this study provides partial support for use of the M-PAC framework to explain acute MVPA among adolescents in real-time and natural contexts.